Writing the City from Below: Graffiti in Johannesburg. Issue 2 (3rd July 2017) - Penfold, Tom
Abstract : Cited as an elusive metropolis, the city of Johannesburg largely resists the imagination. Following on from Lucy Gasser's (2014) reading of Ivan Vladislavić's Portrait with Keys this article considers how graffiti and street art offer ways of "mapping" the city. Focusing on Nuttall and Mbembe's distinction between surface and depth I argue, through a particular focus on the Westdene Graffiti Project, how street art captures some of the tensions in current South Africa and provides new ways of understanding Johannesburg by meeting a map's six key functions: getting to know, re-forming boundaries, making exist, reproducing reality, inscribing meaning and establishing patterns of control. The result is a city written from below.